INFLUENCE OF APPLICATION OF PREVENTIVE WORK SCHEMES ON THE STATE OF ORAL HYGIENE IN SCHOOLCHILDREN WITH DIFFERENT DENTAL STATUS - L.F. Kaskova; T.B. Mandziuk; L.P. Ulasevych; S.Ch. Novikova; I.I. Dronyk (Український стоматологічний альманах)
Caries is a common dental disease that requires regular preventive work, taking into account the factors that lead to its occurrence. Among the controllable risk factors for caries are oral hygiene, nutrition, and a healthy lifestyle, which were included in our schemes of preventive work with children and their parents.